2017
DOI: 10.1155/2017/2180723
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Vascular Change Using Swept-Source Optical Coherence Tomography Angiography: A New Theory Explains Central Visual Loss in Behcet’s Disease

Abstract: Objective To evaluate retinal vascular structural change in ocular Behcet's using optical coherence tomography angiography (OCTA) and fluorescein angiography (FA). Methods An analytic cross-sectional study of 37 eyes of 21 Behcet's uveitic patients was performed. Foveal retinal thickness (FRT), perifoveal hypoperfusion areas in superficial capillary plexus (SCP), and deep capillary plexus (DCP) were measured with swept-source optical coherence tomography and OCTA. FA images were used for assessing the vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 16 publications
0
26
1
Order By: Relevance
“…6,22 Two studies using OCTA described the perifoveal microvascular changes in BD that occur during the active phase. 6,23 However, no study has quantified the microvasculature of the different retinal layers in BD during remission and associated these changes with damage to the outer retina.…”
mentioning
confidence: 99%
“…6,22 Two studies using OCTA described the perifoveal microvascular changes in BD that occur during the active phase. 6,23 However, no study has quantified the microvasculature of the different retinal layers in BD during remission and associated these changes with damage to the outer retina.…”
mentioning
confidence: 99%
“…The work of Somkijrungroj et al also found selective decreases in vascular density for the deep capillary plexus, even in eyes with normal avascular foveal zone as determined by angiography. 20 These findings suggest a degree of macular ischemia may be present in several stages of the disease. Being an important cause of decreased visual acuity, early detection by use of this new technology may be clinically relevant.…”
Section: Original Article » Silva D Et Al Oct-a and Behçetmentioning
confidence: 89%
“…Avascular foveal area of the superficial capillary plexus was found to be significantly smaller than in the deep capillary plexus (0.47 vs. 1.94mm2; p<0.001), with a capillary perfusion ratio between the superficial and deep capillary plexus of 0.57±0.27, correlated with visual acuity, thereby suggesting that the deep capillary plexus may be more intensely affected than the superficial capillary plexus. 20 However, there was no comparison with a control group, limiting the findings of the study. 20 The results of our study, along with the two referred studies, suggest microcirculation alterations at the macular level for these patients, which can be shown by OCT-A.…”
Section: Original Article » Silva D Et Al Oct-a and Behçetmentioning
confidence: 94%
See 2 more Smart Citations